Computer Modeling Wind Turbine Blades with Optimal Parameter (MCIT: Proceedings of International scientific and practical conference, 2023)
The objective of this paper is to develop effective methods of weight optimization for wind turbine blades. New mathematical model based on the application of boundary element method is proposed. Hypersingular integral equations are used to determine the dynamic pressure on the blade. A new version of the nonlinear programming method, based on the usage of adaptive management of optimization procedures, is elaborated. As computer simulation results, the wind turbine blade is obtained with minimal weight